Kualitas Kompos Cacing Tanah Lumbricus rubellus Pada Pakan dan Media yang Berbeda - Endah Novita; Emmy Uthanya Antang; Bambang Supriono Lautt; Panji Surawijaya (Jurnal Kaharati, 2021)
This research aims to 1). Find out the content of N, P, C-Organic, Na-exch, Mg-exch, K-exch, Ca-exch, CEC, and pH-H2O on vermicompost on different feed and media, 2). Find out the effect of feeding types and types medium for growth and development of earthworm colonies Lumbricus rubellus. This study used a factorial Completely Randomized Design (CRD). The first factor is the type of feed with 2 levels: P1 = tofu dregs (150 grams) and P2 = cattle rumen (100 grams) while the second factor is the type of media with 2 levels: G0 = cow manure (1.4 kg) and G1 = cow manure (0.7 kg) + peat soil (0.7 kg). From these treatments there were 4 treatment combinations, each of which was repeated 3 times, in order to obtain 12 experimental units. The weight of worms used is 50 grams per experimental unit. This research was conducted for 3 months from October to December 2019, located at the Experimental Garden of the Department of Agricultural Cultivation, Faculty of Agriculture, Palangka Raya University and Palangka Raya University Analytical Laboratory. The results showed that the results of laboratory analysis of nutrients in worm compost such as pH-H2O, N-total, C-organic, P-Bray, K-exch, Ca-exch, Mg-exch, Na-exch and CEC were found to have different results. There was an interaction between the type of feed and the type of media that had a very significant effect on the pH-H2O variable and the weight of the earthworm Lumbricus rubellus and on a single factor, namely the P-Bray, Ca-exch and Na-exch variables. Whereas in the N-total, C-organic, K-exch and CEC variables there was no significant effect then there was an interaction between the type of feed and the type of media which had a very significant effect on the final weight of Lumbricus rubellus earthworm, namely in the P1G1 treatment with a weight of 155.77 grams, in P1G0 treatment with a weight of 105.58 grams, and in P2G0 treatment with a weight of 90.83 grams, and the weight of Lumbricus rubellus earthworms had no significant effect, namely the P2G1 treatment with a weight of 47.56 grams